Chemical disinfectants and antiseptics. Quantitative suspension test for the evaluation of bactericidal activity of chemical disinfectants and antiseptics used in the veterinary area. Test method and requirements (phase 2, step 1). (27th September 2019) - British Standards Institution,
No abstract available